2016
DOI: 10.1007/s00432-016-2163-y
|View full text |Cite
|
Sign up to set email alerts
|

The relationship of cognitive performance to concurrent symptoms, cancer- and cancer-treatment-related variables in women with early-stage breast cancer: a 2-year longitudinal study

Abstract: Purpose Cognitive dysfunction in women with breast cancer continues to be an area of intense research interest. The prevalence, severity, timing, and cognitive domains that are most affected, as well as the contribution of cancer and its treatments to cognition, remain unresolved. Thus, longitudinal studies are needed that examine cognitive function during different stages of breast cancer treatment and survivorship. This longitudinal trial followed women with early-stage breast cancer, prior to chemotherapy t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
31
0
6

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 34 publications
(38 citation statements)
references
References 53 publications
1
31
0
6
Order By: Relevance
“…A maioria dos estudos explorou, além das funções executivas, outros domínios cognitivos e sintomas concomitantes ao processo da avaliação (Ando-Tanabe, 2014, Askren et al, 2014Chen et al, 2013;Dumas, 2013;Ganz et al, 2003;Jansen, 2011;Kam et al, 2016;Kesler et al, 2011;Koppelmans et al, 2012;Lyon et al, 2016;McDonald et al, 2013;Miao et al, 2016;Park et al, 2015;Piccirillo, et al, 2015;Yao et al, 2016;Zheng et al, 2014). Apenas Kam et al (2016), Miao et al (2016) e McDonald et al (2013) delimitaram-se à investigação e discussão aos aspectos relevantes do funcionamento executivo.…”
Section: Resultsunclassified
See 3 more Smart Citations
“…A maioria dos estudos explorou, além das funções executivas, outros domínios cognitivos e sintomas concomitantes ao processo da avaliação (Ando-Tanabe, 2014, Askren et al, 2014Chen et al, 2013;Dumas, 2013;Ganz et al, 2003;Jansen, 2011;Kam et al, 2016;Kesler et al, 2011;Koppelmans et al, 2012;Lyon et al, 2016;McDonald et al, 2013;Miao et al, 2016;Park et al, 2015;Piccirillo, et al, 2015;Yao et al, 2016;Zheng et al, 2014). Apenas Kam et al (2016), Miao et al (2016) e McDonald et al (2013) delimitaram-se à investigação e discussão aos aspectos relevantes do funcionamento executivo.…”
Section: Resultsunclassified
“…Apenas o teste Stroop, visando à avaliação de controle inibitório, foi o mais utilizado (Chen et al, 2013;Jansen et al, 2011;Kam et al, 2016;Koppelmans et al, 2012;Lyon et al, 2016;Miao et al, 2016;Yao et al, 2016;Zheng et al, 2014). É possível conferir essa variabilidade de métodos de avaliação na Tabela 2.…”
Section: Resultsunclassified
See 2 more Smart Citations
“…Memory impairment is one of the main complaints by patients with breast cancer [83][84][85] and has been linked to inflammatory processes [86,87]. It was demonstrated that breast cancer patients harbouring the IL6-174 GG and TNF-308 GG genotypes had near significant worse memory complaints [61].…”
Section: Memory and Cognitive Functionmentioning
confidence: 99%